The Mediating Effect of Self-confidence on the Impact of Conscious and Unconscious Processes on Risky Investment Intention - Aren, Selim; Hamamci, Hatice Nayman (SAGE PUBLICATIONS INDIA PVT LTD, 2026)
This study investigated the mediating effect of trust and self-confidence on the effects of both conscious processes (coping strategies) and unconscious processes (defence mechanisms) on risky investment intention. In this context, data were collected from 832 participants using an online survey. Exploratory factor and correlation analyses were performed on the collected data, and the research model was tested using structural equation modelling. According to the results of the analysis, both coping strategies and defence mechanisms have an effect on risky investment intention, and self-confidence has a mediating role in this relationship. This study is unique because it explores the effects of both conscious and unconscious processes on financial decisions.
Keywords: Confidence; coping strategies; defence mechanisms; risky investment intention; self-confidence; DEFENSE STYLE; EMOTIONAL INTELLIGENCE; UNIVERSITY-STUDENTS; GENDER-DIFFERENCES; SENSATION-SEEKING; TAKING BEHAVIOR; MECHANISMS; TRUST; PERSONALITY; Business & Economics